Human Mesenchymal Stromal Cells from Different Sources Diverge in Their Expression of Cell Surface Proteins and Display Distinct Differentiation Patterns - Kourosch C. Elahi; Gerd Klein; Meltem Avci-Adali; Karl D. Sievert; Sheila MacNeil; Wilhelm K. Aicher (Hindawi Limited, 2016)
When germ-free cell cultures became a laboratory routine, hopes were high for using this novel technology for treatment of diseases or replacement of cells in patients suffering from injury, inflammation, or cancer or even refreshing cells in the elderly. Today, more than 50 years after the first successful bone marrow transplantation, clinical application of hematopoietic stem cells is a routine procedure, saving the lives of many every day. However, transplanting other than hematopoietic stem and progenitor cells is still limited to a few applications, and it mainly applies to mesenchymal stromal cells (MSCs) isolated from bone marrow. But research progressed and different trials explore the clinical potential of human MSCs isolated from bone marrow but also from other tissues including adipose tissue. Recently, MSCs isolated from bone marrow (bmMSCs) were shown to be a blend of distinct cells and MSCs isolated from different tissues show besides some common features also some significant differences. This includes the expression of distinct antigens on subsets of MSCs, which was utilized recently to define and separate functionally different subsets from bulk MSCs. We therefore briefly discuss differences found in subsets of human bmMSCs and in MSCs isolated from some other sources and touch upon how this could be utilized for cell-based therapies.